The Development of Receptive Language Skills in Early Childhood Through the Chain Message Game at TK Pertiwi Koto Padang, Koto Baru District, Dharmasraya Regency - Respita, Novi; Siska, Widia; Andre, Lesis; Mirdad , Jamal (The Future of Education Journal, 2025)
The promlem in this research is that children’s language skills are less fluent, they cannot listen well and they have limitid vocabulary. The purpose of this study is to determine how teachers implement the chain message game, to determine the development of receptive language skills, and to determine the advantages and disadvantages of the chain message game.This research is a qualitative descriptive study. The subjects were  two teachers and 15 students. Data collection techniques using observation, interview, and documentation. Data validity techniques using triangulation.The results of this study are first, the way teachers implement the chain message game, among others, the teacher asks the children to sit in a circe, the child gets a message from the teacher, the child passes the message to the child next to him, the child who gets a whisper passes it to the friend next to him, and so on until the message returns to the teacher. Second, the development of receptive languange skills of early childhood through chain massage games at Pertiwi Kindergarden is developing very well  (BSB). Of the 15 students, there are 9 children developing very well (BSB) with a percentage of 78 % to 100%, 5 children developed according to expectations (BSH) with a percentage of 60 % to 75 %, and 1 child began to developing (MB) with a percentage of 57 %. Third, the advantages of chain message geme are that it increases student activity, training four skills, attracting students, creates a sense of  happiness, is active, and is confident, has no burden in the learning process, and improves cooperatition. Four, the disadvantages of chain message game are that the class becomes crowded, takes a long time, is too active, and interactions are less conducive